Penguatan Ekonomi Desa Melalui Badan Usaha Milik Desa (Bumdes) Di Kabupaten Sumenep - Ahmad Ghufrony; Nurdody Zakki (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
A Village-Owned Enterprise (BUMDes) is a village business entity established by the village government through a village deliberation (musyawarah desa). It is then managed jointly by the BUMDes administrators and the local village community. The management of BUMDes should remain oriented towards the aspirations of the community, which are then discussed collectively in joint deliberations to establish priority programs aligned with the desires of the local community. The implementation of these programs must be carried out professionally and transparently.However, the challenge of Inadequate Managerial Capability persists. It is not easy for a village to find an individual with superior managerial skills in business management. Even if there are residents who possess such capabilities, they typically already work elsewhere, and if appointed to manage the BUMDes, it would only be on a part-time basis. Consequently, the BUMDes fails to progress and remains stagnant. Conversely, appointing someone with insufficient capacity, as indicated by their track record, is tantamount to steering the BUMDes in a more concerning direction. The purpose of this research is to analyze the contribution of the existence of Village- Owned Enterprises in Sumenep Regency to strengthening the village economy and to identify the supporting and inhibiting factors. This is a qualitative research type with a descriptive approach, and the target output of this research is publication in a scientific journal.